ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG PADA PERPUSTAKAAN STIKOM UYELINDO - Bulan, Semlinda Juszandri (J-Icon : Jurnal Komputer dan Informatika, 2024)
The library has an important role in improving the learning process to prepare quality academic individuals. The level of library visitor satisfaction can be used as an indicator to assess the quality of intangible services. The purpose of this study was to analyze five aspects of service quality in the STIKOM Uyelindo library towards visitor satisfaction. These aspects include tangible evidence, reliability, responsiveness, assurance, and empathy. Respondents in this study were 253 students and lecturers of STIKOM Uyelindo. The method used for data analysis was Partial Least Square (PLS) and was run with SmartPLS software version 3.0. The results showed that reliability, responsiveness, assurance and empathy positively influenced library visitor satisfaction. For libraries to be able to complete book collections with the latest books that are in accordance with the needs of the latest curriculum and expand library space and add facilities such as chairs and computers because the number of students is increasing.